2020
DOI: 10.1101/2020.09.25.20198069
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low-Cost Differential Pressure Spirometry for Emergency Ventilator Tidal Volume Sensing

Abstract: COVID-19 has become a significant burden on the healthcare systems in the United States and around the world, with many patients requiring invasive mechanical ventilation (IMV) to survive. Close monitoring of patients is critical, with total volume per breath (tidal volume) being one of the most important data points. However, ventilators are complex and expensive devices, typically in the range of tens of thousands of US dollars, and are challenging to manufacture, typically requiring months. Solutions which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 7 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…Finally, it should be noted that other authors [27], [29] reported a maximum error between 4% and 5%, when accurately considering all the model variables or applying several regression models. Others [35] have used a single k value for the entire flow range, nevertheless presenting a substantial error for low flow estimation. Our novel method presents various advantages compared to previous methods and an average relative error of up to 4.86%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, it should be noted that other authors [27], [29] reported a maximum error between 4% and 5%, when accurately considering all the model variables or applying several regression models. Others [35] have used a single k value for the entire flow range, nevertheless presenting a substantial error for low flow estimation. Our novel method presents various advantages compared to previous methods and an average relative error of up to 4.86%.…”
Section: Discussionmentioning
confidence: 99%
“…The airflow is regulated and captured in intervals of approximately 1 L/min, starting from 1 and up to 40 L/min; subsequently, then increasing by intervals of 5 L/min until reaching the sensor saturation point, which is around 80 L/min in our case. The data capture occurs in intervals of 1 L/min in the range of 1 L/min up to 40 L/min to reduce the error reported for low-flow estimation [27], [35]. Flow values between 1 and 20 L/min are used as triggers in ventilatory assistance; therefore, having a reasonable estimation of these values is very important.…”
Section: B Proposed Calibration Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Volume calculations are still important for patient care, so in addition to this table for setting the desired delivered volume, a spirometer-based expiratory volume sensor is used on the expiration side of the circuit to measure exhaled volumes. This spirometer-based volume sensor is based on the work of Edmunds et.al [12], who’s work was aimed to help measure gas volumes in ventilators for the COVID-19 pandemic. The O2U ventilator prototype is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%